The impact of water pollution from formal and informal urban developments along the Plankenbrug River on water quality and health risk / J.M. Barnes. - Barnes, J. M. (Johanna Maria) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2003.